Effect of amount of inoculum on the bioleaching of heavy metals from sewage sludge - HUA Yu-mei; LI Wen-hong; CHEN Ying-xu; TIAN Guang-ming (浙江大学学报. 农业与生命科学版, 2005)
Four different amounts of inoculum in mixed sludge, namely 2%, 5%, 10% and 20%, were adopted to investigate the bioleaching of heavy metals from sludge by batch experiment. The result showed that the rate and degree of decrease in pH increased with the amount of inoculum at the beginning. The pH of all samples provided with inoculum approached each other from the fourth day on and were reduced down to about 1.4 at the end. The concentration of sulfate rose rapidly because of the utilization of sulfur as well as a little amount of sulfide of heavy metals by sulfur-oxidizing bacteria in sludge. The inoculum of sulfur-oxidizing bacteria raised the bioleaching rate of Cu, Pb and Zn in sludge and shortened the bioleaching process. The more the amount of inoculum, the shorter the start-up period of bioleaching was. The startup of bioleaching for Zn was faster than that of Cu and Pb. The solubilization of Cu and Zn was relatively stable after the peak, while that of Pb showed a tendency of slight fall. Using 2% inoculum, the most efficient bioleaching of Cu, Pb and Zn occurred at the 5th or 6th day, and thin bioleaching rates were 96.5%, 41.4% and 82.9%, respectively.